Pengaruh Stres Kerja, Kecerdasan Emosional Dan Dukungan Rekan Kerja Terhadap Burnout Guru Di Sekolah SMP Negeri 1 Pematang Bandar Kabupaten Simalungun - Della Indriyani; Normansyah Normansyah (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aims to determine the simultaneous and partial effects of work stress, emotional intelligence, and coworker support on teacher burnout. The research employed a sample of 52 respondents. The data analysis technique used was multiple linear regression. The F-test results showed that Fcount (18.169) > Ftable (2.80), indicating that work stress, emotional intelligence, and coworker support simultaneously affect burnout. The t-test results demonstrated that work stress has a positive and significant effect on burnout because tcount (5.543) > ttable (2.00958), emotional intelligence has a negative and significant effect on burnout because tcount (-5.534) < -ttable (-2.00958), and coworker support has a negative and significant effect on burnout because tcount (-2.910) < -ttable (-2.00958). The coefficient of determination test (Adjusted R Square) showed a value of 0.502, indicating that the independent variables consisting of work stress, emotional intelligence, and coworker support were able to explain burnout by 50.2%, while the remaining 49.8% was explained by other variables not included in this study.